The Influence of Pedagogic Competence, Academic Supervision, and Organizational Culture, on Performance Through Teacher Work Motivation at SMPN 1 Kaloran - Astuti, Heni Purwo; Yulianto, Arief; Widiyanto, Widiyanto (Educational Management, 2022)
This research aims to analyze the influence of academic supervision, organizational culture, and pedagogical competence on teacher performance through work motivation as an intervening variable at SMPN 1 Kaloran. Teacher performance is the result of a teacher's work or work performance based on their ability to manage teaching and learning activities in the classroom. Many factors influence teacher performance, including academic supervision, organizational culture, pedagogical competence, and work motivation. This research uses a quantitative approach. The population is 40 teachers of SMPN 1 Kaloran. The sampling uses the total sampling method. The research instrument is a questionnaire that was first tested for reliability and validity. The data investigation for hypothesis testing adopt] path analysis and the Sobel test to investigate the mediating variable. The findings show that academic supervision, organizational culture, and pedagogical competence have a significant influence on work motivation. Teacher performance affected by academic supervision, organizational culture, and pedagogical competence, mediated by teacher work motivation. Based on these findings, teacher performance can be improved through some improvements in academic supervision, organizational culture, pedagogical competence, and work motivation.